PENGARUH EARNING MANAGEMENT DAN TAX MANAGEMENT TERHADAP BOOK-TAX DIFFERENCES YANG DIMODERASI OLEH PENGAWASAN KOMITE AUDIT - Sitorus, Riris Rotua; Lawahizh, Yusriyya Nur (Universitas 17 Agustus 1945 Jakarta, 2019)
One topic that attracts interesting now in the field of tax accounting is the book-tax differences. This occurs because of the basic differences in the preparation contained in the calculation of earnings between commercial and taxation, causing a difference between the amount of income before tax (accounting profit) with income after tax (fiscal profit) or referred to as book-tax differences.The number of samples that will be used in the study are 46 property companies located on the Indonesia Stock Exchange (BEI) for the 2015-2017 period. Data processing is done using path analysis techniques at a 5% significance level. Earning Management does not have a significant effect on book tax differences, while tax management has a significant influence on book tax differences.The audit committee has no significant effect on book tax differences. Supervision of the audit committee does not strengthen the influence of earnings management and tax management on book tax differences.Keyword: Book-tax Differences, ETR, Earning Management, audit committee